2020
DOI: 10.35940/ijmh.i0846.054920
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Carrying Capacity Lands for Food Agriculture Based on Land Degradation in Pagar Alam City - Indonesia

Abstract: The purpose of this research is a) analyzing the Land of paddy land change in South Sumatera province, and b) analyzing the capacity to support agricultural land-based food crops degraded land in Pagar Alam City. This research uses a quantitative descriptive approach, with variables are about changing land-use using the Geographic information systems (GIS). The results showed that the most extensive land-use in 2007 was mixed bush dryland agriculture (40339.45 Ha), while in 2019 was paddy land (24195.47 Ha). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…Also, croplands generally have a flat morphology, good accessibility, and are located close to water resources, which makes development relatively easy. In addition, unlike built-up areas, converting croplands does not require evictions, which would require greater costs and time [6].…”
Section: Land Use Conversion Into a Toll Road From 2011 To 2020mentioning
confidence: 99%
“…Also, croplands generally have a flat morphology, good accessibility, and are located close to water resources, which makes development relatively easy. In addition, unlike built-up areas, converting croplands does not require evictions, which would require greater costs and time [6].…”
Section: Land Use Conversion Into a Toll Road From 2011 To 2020mentioning
confidence: 99%
“…The production was higher than the demand for one year (104,211 tons per year), which shows an indication of a production surplus. Furthermore, the calculation of food needs (Wilis et al, 2020) found an annual production of 327.476 kg per capita or equivalent to 897.19 gr per capita.…”
Section: Supply and Demand Balancementioning
confidence: 99%
“…Considering this strategic position, the government needs to consider the allocation of more industrial estates in Batang Regency or instead find alternative allocations to outside the region (KFMAP, 2021). Planning for rice production needs estimate without considering the main potential of land resources can lead to degradation (Wilis et al, 2020).…”
Section: Supply and Demand Balancementioning
confidence: 99%